Oleraceins from Portulaca oleracea leaves: Quali-quantitative determination and antioxidant potential - Ciro Cannavacciuolo; Assunta Napolitano; Verena M. Dirsch; Elke H. Heiss; Milena Masullo; Sonia Piacente (Current Research in Food Science)
Portulaca oleracea L. (purslane) is a spontaneous herb whose shoots are appreciated in the Mediterranean and Asian diets for their fresh flavor and crunchy texture. In addition to PUFA (PolyUnsaturated Fatty Acids), it contains unusual polyphenolic alkaloids called oleraceins. This work aimed at investigating the oleracein profile of different ‘green’ extracts of the leaves of Portulaca oleracea and evaluating their antioxidant capacity. An LC-MS screening of different extracts revealed the infusion as the extract richest in oleraceins. Qualitative and quantitative analysis of oleraceins in this extract resulted in the identification of three polyphenolic alkaloids never reported before and in the definition of oleracein A as the most abundant alkaloid. An oleracein-enriched fraction from the infusion and its hydrolysed derivative exhibited radical scavenging activity in vitro and led to activation of the Nrf2 pathway in cells without apparent cytotoxicity. Thus, its oleracein content may make purslane a potential nutraceutical for alleviating redox distress.